Қарақалпақ тилинде «ақ» келбетлигиниң символлық мәнилери (FAN va JAMIYAT, 2024)
This article provides information about the emergence of the color terms in human society, the scope of the usage of color adjectives in the modern Karakalpak language, the appearance, symbolic meanings of colors and the emergence of colors related to the customs, traditions, and beliefs of the people.